A Physical Unclonable Function With Redox-Based Nanoionic Resistive Memory - Kim, Jeeson; Ahmed, Taimur; Nili, Hussein; Yang, Jiawei; Jeong, Doo Seok; Beckett, Paul; Sriram, Sharath; Ranasinghe, Damith C.; Kavehei, Omid (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
Emerging non-volatile reduction-oxidation (redox)-based resistive switching memories (ReRAMs) exhibit a unique set of characteristics that make them promising candidates for the next generation of low-cost, low-power, tiny, and secure physical unclonable functions (PUFs). Their underlying stochastic ionic conduction behavior, intrinsic nonlinear current-voltage characteristics, and their well-known nano-fabrication process variability might normally be considered disadvantageous ReRAM features. However, using a combination of a novel architecture and special peripheral circuitry, this paper exploits these non-idealities in a physical one-way function, nonlinear resistive PUF, potentially applicable to a variety of cyber-physical security applications. We experimentally verify the performance of valency change mechanism (VCM)-based ReRAM in nano-fabricated crossbar arrays across multiple dies and runs. In addition to supporting a massive pool of challenge-response pairs (CRPs), using a combination of experiment and simulation our proposed PUF exhibits a reliability of 98.67%, a uniqueness of 49.85%, a diffuseness of 49.86%, a uniformity of 47.28%, and a bit-aliasing of 47.48%.